Evaluation of European electric vehicle support schemes - Fabian Kley; Martin Wietschel; David Dallinger (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2010)
Electric vehicles can reduce carbon dioxide emissions, increase energy efficiency, and help to reduce the dependency on oil imports. However, today's technical and economic challenges are preventing mass-market adoption. In order to create an early market and support economies of scale in production, some European countries have already established support schemes. This research study aims to provide an overview of the existing support schemes in Europe and to assess them using four criteria: effectiveness, efficiency, practicability, and political acceptance. The study concludes with an impact analysis of today's economic support schemes which considers the total costs of ownership. While one-time support schemes help to reduce the large initial investments for EVs, recurring instruments are often more effective and efficient but also smaller in volume. The comparison of the different regional incentive schemes reveals that EVs today are only economically attractive in Denmark and Norway, but at relatively high prices. Thus, regulators need to increase the volume and efficiency of the support schemes, establish high scoring instruments, and align these on a European scale. In addition, non-monetary support, e.g. free-parking, can help to overcome technical or smaller economic hurdles.
urn:nbn:de:0011-n-1450075
Keywords: 330; Elektrofahrzeug; Wirtschaftsförderung; Wirkungsanalyse; Vergleich; Europa